Differentiating African teams from European teams: identifying the key performance indicators in the Fifa World Cup 2018 - Kubayi, A.; Toriola, A. (Journal of Human Kinetics, 2020)
Soccer is the most popular sport in the world. Despite this global popularity, European teams in contrast to African ones, have dominated the Fédération Internationale de Football Association (FIFA) World Cup tournaments for many decades. Therefore, the aim of this study was to examine the performance indicators that differentiated between African and European teams in the 2018 FIFA World Cup. Thirty matches played by five European (n = 15) and five African teams (n = 15) from the group stages of the World Cup were analysed using the InStat video system. The results showed that European teams had higher averages than African teams on the following performance variables: total shots, shots on target, goals scored from open play and set pieces, ball possession, short passes, medium passes, total passes, accurate passes and corner kicks. Therefore, soccer coaches should take note of these findings as they could serve as a benchmark for African teams to set trends and improve their performance at FIFA World Cup tournaments.